RETRACTED: The Effect of Age Level, Education Level, Work Environment and Compensation on Work Productivity of Rumah Sakit Umum Pusat (RSUP) Persahabatan - Annisa Feby Yolanda; Herry Krisnandi; Kumba Digdowiseiso (Journal of Social Science, 2024)
This study aims to determine the effect of age level, education level, work environment and compensation on work productivity at the Friendship General Hospital (RSUP). The data source of this study used primary data in the form of a questionnaire, the data of this study was given to 339 respondents at Persahabatan Hospital. In taking the sample for this research using random sampling method. The data analysis technique used is multiple linear regression and hypothesis testing using t-statistics that have been processed in SPSS 23 to test the regression coefficients. Based on the results of the study showed that Age Level (X1) had a negative and insignificant effect, Education Level (X2) had a positive but not significant effect, Work Environment (X3) had a positive and significant effect on Work Productivity, Compensation (X4) had a positive and significant effect on Productivity.